The Undergraduate English Students’ Perception, Plan, and Implementation of Critical Thinking Skills in Their Presentation - Erito, Silvia Nanda Putri; Linggar Bharati, Dwi Anggani; Astuti, Puji (English Education Journal, 2021)
Previous studies shows that several learning strategies have been used to promote critical thinking skills for students at the university level, the most frequently used is presentation. The students in the third semester of the English department in IAIN Pekalongan have distinctive responses regarding their critical thinking skills in their presentation. This study aimed to explain students’ perception, plan and implementation in their use of critical thinking skills in their presentation. This study was qualitative case study. The data gathered by classroom observation, questionnaires, and interviews. The findings showed (1) The students positively perceived their use of critical thinking skills in their presentation, they believed that critical thinking skills help them to enable their presentation, English skills, and performance (2) the students plan their critical thinking skills by preparing the schema, skills, and practicing (3) the implementation of critical thinking skills in students' presentation by combining students' awareness, activeness, and learning style. Theoretically, critical thinking skills are fundamental to be implemented in higher education students. Practically, the result of this study gave benefit for the lecturer in giving students challenging tasks that encourage them to use their critical thinking skills. Pedagogically, the implementation of critical thinking skills in students’ presentations needs a student-lecturer relationship.